EFEKTIVITAS PENGGUNAAN SIMBOL GARUDA DAKAM PEMBELAJARAN PANCASILA DI KELAS 2 SDI AL-IMAN - Ahmad Arif Fadilah; Anita Dewi; Salwa Pradita (Sindoro: Cendikia Pendidikan, 2024)
This research aims to analyze the effectiveness of using the Garuda symbol in Pancasila learning in class 2 of SDI AL-IMAN. The method used is quantitative research with an experimental design, where students are divided into two groups: one group is taught to use the Garuda symbol as a learning medium, while the other group uses conventional methods. Data was collected through learning results tests and questionnaires to measure students' understanding of Pancasila values. The results of the analysis show that the use of the Garuda symbol significantly increases students' understanding of Pancasila, as well as fostering a sense of love for their homeland and national identity. It is hoped that these findings can contribute to the development of more effective learning methods in Pancasila education at the elementary level.